Expert group recommendation on inhaled mucoactive drugs in pediatric respiratory diseases: an Indian perspective - Singh, Meenu; Varkki, Sneha; Kinimi, Ilin; Das, Rashmi R.; Goyal, Jagdish Prasad; Bhat, Mushtaq; Dayal, Rajeshwar; Kalyan, Pawan; Gairolla, Jitender; Khosla, Indu (Frontiers in Pediatrics, 2023)
Background: Currently, there are no guidelines or consensus statements about the usage of inhaled mucoactive drugs in pediatric respiratory disease conditions from an Indian perspective.Objective: To develop a practical consensus document to help pediatricians in clinical decisionmaking when choosing an appropriate mucoactive drug for the management of specific respiratory disease conditions. Methods: A committee of nine experts with significant experience in pediatric respiratory disease conditions and a microbiological expert constituted the panel. An electronic search of the PubMed/MEDLINE, Cochrane Library, Scopus, and Embase databases was undertaken to identify relevant articles. Various combinations of keywords such as inhaled, nebulized, mucoactive, mucolytic, mucokinetic, expectorants, mucoregulators, mucociliary clearance, respiratory disorders, pediatric, cystic fibrosis (CF), non-CF bronchiectasis, acute wheezing, asthma, primary ciliary dyskinesia (PCD), critically ill, mechanical ventilation, tracheomalacia, tracheobronchomalacia, esophageal atresia (EA), tracheoesophageal fistula (TEF), acute bronchiolitis, sputum induction, guideline, and management were used. Twelve questions were drafted for discussion. A roundtable meeting of experts was conducted to arrive at a consensus. The level of evidence and class of recommendation were weighed and graded.Conclusions: Inhaled mucoactive drugs (hypertonic saline, dry powder mannitol, and dornase alfa) can enhance mucociliary clearance in children with CF. Experts opined that hypertonic saline could be beneficial in non-CF bronchiectasis, acute bronchiolitis, and PCD. The current state of evidence is inadequate to support the use of inhaled mucoactive drugs in asthma, acute wheezing, tracheomalacia, tracheobronchomalacia, and EA with TEF.